2x +7 = x + 18 (separated variable x of constants)
2x - x = 18 -7 (simplification)
x = 11
Verification
2(11) + 7 = 11 + 18
22 + 7 = 29
29 = 29
2007-09-10 14:35:55
·
answer #1
·
answered by frank 7
·
0⤊
0⤋
U hav to get the Xs on one side and the numbers on the different 2x+7=x+18 Then flow the 7 to after the 8 (once you progression something to the different side the sign changes so a favorable extensive type will exchange to a detrimental extensive type and vies versa) So it is going to likely be 2x=x+18-7 then you could paintings out 18-7=11 So it could be 2x=x+11 then you progression the x to after the 2x ( the helpful x will exchange to a detrimental) So it could be 2x-x=11 Then paintings out 2x-x=x So it could be x=11 wish it fairly is comprehensible :)
2016-10-04 08:41:34
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
If you convert the equation so all of the x's are on one side and the other #'s are one the other you would have 2x-x=18-7 (remember when you move a # from one side to the other it will be its opposite...negative becomes positive and visa versa.)
then follow through with the math 1x=11...x=11 Hope that helps;)
2007-09-10 14:39:53
·
answer #3
·
answered by Rasta 3
·
0⤊
0⤋
in order to solve you need to combine like terms;
2x+7=x+18
first step:
you do the opposite that the sight for ex : +7 gets subrtacted form its side and then subtracted from the 18
so it would look like: 7-18=11
step 2:
so now you have 2x=x+11
so you subrtact the x from the opposite of the equal sign looking like:
x because 2x-x= 1x (or ) x=11
so your answer would be x=11
Make sence??
2007-09-10 14:38:10
·
answer #4
·
answered by valleygirl_1986 3
·
0⤊
0⤋
First gather your terms onto one side. Remember that when things switch from one side of the equation to the other, the sign changes...so
2x + 7 = x + 18
2x - x = -7 +18
x = 11
Check your answer
2(11) + 7 = 11 + 18
29 = 29
voila!
2007-09-10 14:35:36
·
answer #5
·
answered by vitaeterna2004 2
·
0⤊
0⤋
Subtract x from both sides. This leaves you with one "x" term, on the left. Then just subtract 7 form both sides which leaves you with X=11
2007-09-10 14:34:43
·
answer #6
·
answered by uncutshadow92 1
·
0⤊
0⤋
2x+7=x+18
3x+7=18
-7= -7
x=11
2007-09-10 14:38:01
·
answer #7
·
answered by caligirl1922 1
·
0⤊
1⤋
First you need to get the x's together, so we subtract x from the right side and 7 from the left, so....
x=11
2007-09-10 14:36:16
·
answer #8
·
answered by Kaylin 4
·
0⤊
0⤋
2x+7=x+18
2x=x+18-7
2x=x+11
x=11
2007-09-10 14:38:32
·
answer #9
·
answered by ogocephalus 1
·
0⤊
0⤋
Subtract x from both sides. This leaves you with one "x" term, on the left. Then just subtract 7 form both sides.
2007-09-10 14:32:44
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋